In Vitro Antimicrobial Effectiveness of Calcium Hydroxide and Its Combination with Sodium Hypochlorite against Enterococcus Faecalis and Candida Albicans - Mohamed Issa; Najwa Marghani (AlQalam Journal of Medical and Applied Sciences, 2024)
The aim of this in vitro study was to evaluate and compare the antimicrobial effect of calcium hydroxide (〖Ca(OH)〗_2) and its combination with 5% sodium hypochlorite (NaOCL) as intracanal medicaments against Enterococcus faecalis (E. faecalis) and Candida albicans after one, three and seven days. Inoculate of these organisms (E. faecalis and candida albicans) were used to make lawn cultures on Mueller-Hinton with 5% defibrinated sheep blood agar and Mueller-Hinton agar. 60 wells with a depth of 4 mm were prepared for E. faecalis. Then 20 wells filled with 〖Ca(OH)〗_2, 20 wells filled with combination of 〖Ca(OH)〗_2 and 5% NaOCL, and last 20 wells were filled with distilled water as control. A similar procedure was conducted for Candida albicans. The zone of inhibition for each material used against a particular organism were measured and recorded after 1, 3, and 7 days. 〖Ca(OH)〗_2 in combination with 5% NaOCL is more effective than 〖Ca(OH)〗_2 alone against E. faecalis and Candida albicans at different time periods. E. faecalis was more resistant than Candida albicans to intracanal medicaments used. The antimicrobial effect depends on how long it remains inside the root canal. Mixing of 〖Ca(OH)〗_2 with 5% NaOCL had antimicrobial effect on both E. faecalis and Candida albicans and it was more effective against Candida albicans. كان الهدف من هذه الدراسة المعملية هو تقييم ومقارنة التأثير المضاد للميكروبات لهيدروكسيد الكالسيوم وتوليفته مع هيبوكلوريت الصوديوم 5% كأدوية داخل القناة ضد المكورات المعوية البرازية و المبيضات المبيضة بعد يوم وثلاثة وسبعة أيام . تم استخدام التلقيح من هذه الكائنات الحية (المكورات المعوية البرازية و المبيضات المبيضة) في زراعة العشب في مولر-هينتون باستخدام أجار دم الأغنام منزوع الرجفان بنسبة 5% وأجار مولر-هينتون. تم تحضير 60 بئراً بعمق 4 ملم للمكورات المعوية البرازية . ثم تم ملء 20 بئرًا بهيدروكسيد الكالسيوم، و20 بئرًا مملوءة بمزيج من هيدروكسيد الكالسيوم و5% هيبوكلوريت الصوديوم ، وتم ملء آخر 20 بئرًا بالماء المقطر كعنصر تحكم. تم إجراء إجراء مماثل للمبيضات المبيضة. تم قياس وتسجيل منطقة التثبيط لكل مادة مستخدمة ضد كائن حي معين بعد 1، 3، و7 أيام . يعتبر هيدروكسيد الكالسيوم مع 5% هيبوكلوريت الصوديوم أكثر فعالية من هيدروكسيد الكالسيوم وحده ضد المكورات المعوية البرازية والمبيضات المبيضة في فترات زمنية مختلفة. كانت المكورات المعوية البرازية أكثر مقاومة من المبيضات المبيضة للأدوية المستخدمة داخل القناة. يعتمد التأثير المضاد للميكروبات على المدة التي تبقى فيها داخل قناة الجذر. كان لخلط هيدروكسيد الكالسيوم مع 5% هيبوكلوريت الصوديوم تأثير مضاد للميكروبات على كل من المكورات المعوية البرازية والمبيضات المبيضة وكان أكثر فعالية ضد المبيضات المبيضة